Erratum for Janssen et al., "Evolution of Colistin Resistance in the Klebsiella pneumoniae Complex Follows Multiple Evolutionary Trajectories with Variable Effects on Fitness and Virulence Characteristics": Evolution of colistin resistance in the klebsiella pneumoniae complex follows multiple evolutionary trajectories with variable effects on fitness and virulence characteristics (Antimicrobial Agents and Chemotherapy (2021) 65:1 (e01958-20) DOI: 10.1128/AAC.01958-20) - Janssen, Axel B.; Doorduijn, Dennis J.; Mills, Grant; Rogers, Malbert R.C.; Bonten, Marc J.M.; Rooijakkers, Suzan H.M.; Willems, Rob J.L.; Bengoechea, Jose A.; Van Schaik, Willem (American Society for Microbiology, 2021)
Volume 65, no. 1, e01958-20, 2021, https://doi.org/10.1128/AAC.01958-20. Figure 2: The MICs of colistin for axenic strains were inadvertently omitted. The correct figure is shown below.
Keywords: Taverne; Pharmacology (medical); Infectious Diseases; Pharmacology; Published Erratum; Journal Article